Injectable Excipients as Novel Influenza Vaccine Adjuvants - Feng, Huapeng; Yamashita, Makoto; da Silva Lopes, Tiago Jose; Watanabe, Tokiko; Kawaoka, Yoshihiro (Frontiers in Microbiology, 2019)
Influenza outbreaks can be either seasonal or pandemic. Vaccination is an effective strategy to control influenza; however, the efficacy of the currently available inactivated influenza virus vaccines is suboptimal, especially in the elderly. Vaccine efficacy can be improved by the addition of adjuvants, but few adjuvants have been approved for human vaccines. To explore novel, safe, and effective adjuvants for influenza vaccines, here we used a mouse model to screen 46 injectable drug additives approved in Japan. Of these 46 candidates, we identified 20 compounds that enhanced the efficacy of the split influenza HA vaccine against lethal virus challenge. These 20 compounds included 15 novel adjuvant candidates and 5 compounds with previously reported adjuvant effects for other antigens but not for influenza vaccine. Given that these additives are already approved for human use, the hurdle for their clinical use as novel and effective adjuvants for influenza or other vaccines is lower than for other adjuvant candidates whose safety profiles are unknown.